Endogenous Taxation in Ongoing Internal Conflict: The Case of Colombia (2018)
Recent empirical evidence suggests an ambiguous relationship between internal conflicts, state capacity, and tax performance. In theory, internal conflict should create strong incentives for governments to develop the fiscal capacity necessary to defeat rivals. We argue that one reason that this does not occur is because internal conflict enables groups with de facto power to capture local fiscal and property rights institutions. We test this mechanism in Colombia using data on tax performance and property rights institutions at the municipal level. Municipalities affected by internal conflict have tax institutions consistent with the preferences of the parties dominating local violence. Those suffering more right-wing violence feature more land formalization and higher property tax revenues. Municipalities with substantial left-wing guerrilla violence collect less tax revenue and witness less land formalization. Our findings provide systematic evidence that internal armed conflict helps interest groups capture municipal institutions for their own private benefit, impeding state-building. Copyright © American Political Science Association 2018.